Senam Kaki Diabetes terhadap Derajat Diabetic Peripheral Neuropathy (DPN) pada Pasien Diabetes Mellitus Tipe 2 - Ida Karyati; Hotma Rumohorbo; Novie E Mauliku; Cecep Eli Kosasih (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study aims to determine the effectiveness of diabetic foot exercises on DPN values ​​in DMT-2 patients. The method used is a quasi-experiment with Pretest-Postest with a control group design. The study results showed that in the intervention group using Wilcoxon, 0.000 was obtained, and 0.001 in the control group. Still, if you look at the clinical results of a difference of less than 10, there is no significant difference in the degree of DPN before and after the intervention. The results of the study with the Mann-Whitney test showed that diabetic foot exercises are effective in reducing the degree of DPN (p = <0.05), where the intervention group had a lower degree of DPN (12.24) compared to the control group (30.76). There is a difference in the degree of DPN between the intervention and control groups, with a p = 0.001. In conclusion, foot exercises effectively reduce the degree of diabetic peripheral neuropathy in patients with type 2 diabetes mellitus at Dustira Hospital Cimahi. Keywords: Diabetes Mellitus, Diabetic Peripheral Neuropathy, Foot Exercises